Function-impairing polymorphisms of the hepatic uptake transporter SLCO1B1 modify the therapeutic efficacy of statins in a population-based cohort. Issue 1 (January 2015) - Meyer zu Schwabedissen, Henriette E.; Albers, Martin; Baumeister, Sebastian E.; Rimmbach, Christian; Nauck, Matthias; Wallaschofski, Henri; Siegmund, Werner; Völzke, Henry; Kroemer, Heyo K.
<x xml:space="preserve">Abstract</x> Background The efficacy of statins, which are used commonly in primary and secondary prevention of cardiovascular diseases, shows a wide range of interindividual variability. Genetic variants of OATP1B1, a hepatic uptake transporter, can modify access of statins to its therapeutic target, thereby potentially altering drug efficacy. We studied the impact of genetic variants of OATP1B1 on the lipid-lowering efficacy of statins in a population-based setting. Materials and methods The basis of the analysis was the Study of Health in Pomerania, a cohort of 2732 men and women aged 20–81 years. Included in the statistical analysis to evaluate the impact of OATP1B1 on therapeutic efficacy of statins were 214 individuals diagnosed with dyslipidaemia during initial recruitment and receiving statins during the 5-year follow-up. Results Analysing the impact of the OATP1B1 genotype, we observed a trend for lower statin-induced total cholesterol reduction in carriers of the SLCO1B1 512C variant. Restricting the analysis to patients receiving simvastatin, pravastatin, lovastatin and fluvastatin indicated a statistically significant association of the OATP1B1 genotype on lipid parameters at the 5-year follow-up. No such effect was observed for atorvastatin. Calculation of achievement of treatment goals according to the NCEP-ATPIII guidelines showed a lower rate of successful treatment when harbouring the mutant allele for patients taking simvastatin (46.7 vs. 73.9%). A similar trend was observed for pravastatin (34.4 vs. 70.4%). Conclusion Genetic variants of OATP1B1 leading to impaired hepatic uptake of statins translated into reduced drug efficacy in a population-based cohort.